Can a reresection be avoided after initial en bloc resection for high-risk nonmuscle invasive bladder cancer? A systematic review and meta-analysis - Xu, Jiangnan; Xu, Zhenyu; Yin, HuMin; Zang, Jin (Frontiers in Surgery, 2022)
Background This study aims to evaluate the effectiveness of en bloc resection for patients with nonmuscle invasive bladder cancer (NMIBC) and explore whether a reresection can be avoided after initial en bloc resection. Material and methods We conducted research in PubMed, EMBASE, Cochrane Library, and Web of Science up to October 12, 2021, to identify studies on the second resection after initial en bloc resection of bladder tumor (ERBT). R software and the double arcsine method were used for data conversion and combined calculation of the incidence rate. Results A total of 8 studies involving 414 participants were included. The rate of detrusor muscle in the ERBT specimens was 100% (95%CI: 100%–100%), the rate of tumor residual in reresection specimens was 3.2% (95%CI: 1.4%–5.5%), and the rate of tumor upstaging was 0.3% (95%CI: 0%–1.5%). Two articles compared the prognostic data of the reresection and non-reresection groups after the initial ERBT. We found no significant difference in the 1-year recurrence-free survival (RFS) rate (OR = 1.44, 95%CI: 0.67–3.09, P = 0.35) between the two groups nor in the rate of tumor recurrence (OR = 0.72, 95%CI: 0.44–1.18, P = 0.2) or progression (OR = 0.98, 95%CI: 0.33–2.89, P = 0.97) at the final follow-up. Conclusions ERBT can almost completely remove the detrusor muscle of the tumor bed with a very low postoperative tumor residue and upstaging rate. For high-risk NMIBC patients, an attempt to appropriately reduce the use of reresection after ERBT seems to be possible.